Glycaemic control of Type 1 diabetes in clinical practice early in the 21st century: an international comparison. Issue 8 (21st February 2015) - McKnight, J. A.; Wild, S. H.; Lamb, M. J. E.; Cooper, M. N.; Jones, T. W.; Davis, E. A.; Hofer, S.; Fritsch, M.; Schober, E.; Svensson, J.; Almdal, T.; Young, R.; et al.
Abstract Aims Improving glycaemic control in people with Type 1 diabetes is known to reduce complications. Our aim was to compare glycaemic control among people with Type 1 diabetes using data gathered in regional or national registries. Methods Data were obtained for children and/or adults with Type 1 diabetes from the following countries (or regions): Western Australia, Austria, Denmark, England, Champagne‐Ardenne (France), Germany, Epirus, Thessaly and Thessaloniki (Greece), Galway (Ireland), several Italian regions, Latvia, Rotterdam (The Netherlands), Otago (New Zealand), Norway, Northern Ireland, Scotland, Sweden, Volyn (Ukraine), USA and Wales) from population or clinic‐based registries. The sample size with available data varied from 355 to 173 880. Proportions with HbA1c < 58 mmol/mol (< 7.5%) and ≥ 75 mmol/mol (≥ 9.0%) were compared by age and sex. Results Data were available for 324 501 people. The proportions with HbA1c 58 mmol/mol (< 7.5%) varied from 15.7% to 46.4% among 44 058 people aged < 15 years, from 8.9% to 49.5% among 50 766 people aged 15–24 years and from 20.5% to 53.6% among 229 677 people aged ≥ 25 years. Sex differences in glycaemic control were small. Proportions of people using insulin pumps varied between the 12 sources with data available. Conclusion These results suggest that there are substantial variations in glycaemic control among people with Type 1 diabetes between the data sources and that there is room for improvement in all populations, especially in young adults.